Does the use of low-level light therapy postoperatively reduce pain, oedema, and neurosensory disorders following orthognathic surgery? A systematic review - Barbosa, L. M. (2022)
The aim of this study was to evaluate the efficacy of low-level light therapy (LLLT) in improving pain, oedema, and neurosensory disorders of the inferior alveolar nerve (IAN) after orthognathic surgery. This systematic review was performed in compliance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Searches were conducted in the PubMed, Embase, and Web of Science databases for randomized clinical trials (RCTs) published up to September 2020. After evaluating eligibility, 15 RCTs were selected. None of the studies reported an evaluation of all of the outcomes within the same publication. It was possible to determine the effect of LLLT in controlling pain following orthognathic surgery. Of the three studies evaluating this outcome, all observed a positive effect. Of the four studies that evaluated oedema, two found a positive effect. Of the 11 studies that evaluated neurosensory disorders of the IAN, all of them observed a positive effect, at least in one of the sensory evaluation tests. A meta-analysis was not possible due to the heterogeneity across studies. Considering the limitations of this review, but given the fact that LLLT is a minimally invasive intervention, its use merits consideration in immediate postoperative orthognathic surgery.